(untitled) (Latakia University Journal -Medical Sciences Series, 2023)
Objective: The aim of the study is to determine the microbiological profile of DA-HAIs in adult patients who spent over 48 hours in the ICU unit located in Tishreen University Hospital in Lattakia between June 2021 and December 2022. Materials and methods: The study included 142 culture-positive samples, bacterial isolates were diagnosed based on the morphological and biochemical characteristics using API 20E strips in some samples. The identification of antibiotic resistance levels was performed with the disc diffusion method (Kirby-Bauer) in Muller Hinton agar. Results: The most common isolated microorganism was Pseudomonas aeruginosa (23.94%) followed by Staphylococcus aureus (19.72%), Escherichia coli (19.1%), Klebsiella sp. (12.68%), Acinetobacter sp. (9.86%), Coagulaase-negativ staphylococci (7.75%), Proteus sp. (4.32%) and Streptococcus pneumoniae (2.82%) as the least widespread isolates. 59.8% (84/142) of the isolates were classified as multi-drug resistant (MDR). Catheter-associated Urinary Tract Infections was the most frequently infection found in our Intensive care unit. A trend of increasing resistance of gram-negative bacilli to penicillins, cephalosporins, and fluoroquinolones was observed ranging from 66%-76%, with a resistance rate higher than 50% to carbapenems and aminoglycosides, which compels us to resort to polymyxins. While the percentages of Gram-positive bacteria resistance allow carbapenems (20.48%) and glycopeptides (32.3%) to be the best options in the event of diagnosis of a Gram-positive pathogen.